Comparative study on seismic performance of concrete-filled double skin tubular piers and hollow concrete piers: Experimental and analytical. (March 2023) - Li, Zhong-Xian; Du, Chunyu; Liu, Dong; Liang, Xiao; Zhao, Bo
Abstract: Hollow bridge piers with concrete-filled double skin tubular (CFDST) section could offer more efficient fabrication and better confinement effect, but increase construction cost with the use of steel tubes if compared to regular hollow concrete bridge piers. Although hollow concrete piers and CFDST piers have been the focus of the existing experimental and numerical studies, there is limited information available regarding to the seismic performance comparisons of the two systems while considering the cost perspective. Therefore, a comparative study was carried out in the current study to compare the seismic performance of the two designs quantitatively, while considering the cost effectiveness. The experimental results of the two designs were compared in terms of lateral force bearing capacity, deformation capacity, energy dissipation, stiffness degradation, residual displacement, and performance per cost ratio. It has been found that the lateral force bearing capacity, the displacement ductility, the effective pier flexural stiffness and the performance per cost ratio of CFDST pier increased by 50.2%, 16.7%, 22.9% and 36.5%, respectively, while the residual drift ratio reduced by 33.3% at a large drift ratio of 3.0%. In addition, the seismic performance of another two CFDST piers with different diameter-to-thickness ratio of outer steel tubes and hollow ratio was studied through cyclic lateral loading tests. A verified finite element model was also developed to further conduct parametric study to fully investigate the influence of the diameter-to-thickness ratio of outer steel tubes and hollow ratio on the seismic performance of CFDST piers. Experimental and numerical results have found that the diameter-to-thickness ratio of outer steel tubes is one of the most important factors that influences the seismic performance of CFDST piers. In contrast, the hollow ratio significantly influences the deformation capacity of CFDST piers without significantly affecting the lateral force bearing capacity. The diameter-to-thickness ratio of outer steel tubes is suggested to take between 60 and 150, and the hollow ratio is suggested to take between 0.5 and 0.7 for cost effectiveness and ductile seismic design purposes of CFDST bridge piers.